Mitochondrial Calcium Uniporter Deficiency in Zebrafish Causes Cardiomyopathy With Arrhythmia - Langenbacher, Adam D.; Shimizu, Hirohito; Hsu, Welkin; Zhao, Yali; Borges, Alexandria; Koehler, Carla; Chen, Jau-Nian (Frontiers in Physiology, 2020)
Mitochondrial Ca2+ uptake influences energy production, cell survival, and Ca2+ signaling. The mitochondrial calcium uniporter, MCU, is the primary route for uptake of Ca2+ into the mitochondrial matrix. We have generated a zebrafish MCU mutant that survives to adulthood and exhibits dramatic cardiac phenotypes resembling cardiomyopathy and sinus arrest. MCU hearts contract weakly and have a smaller ventricle with a thin compact layer and reduced trabecular density. Damaged myofibrils and swollen mitochondria were present in the ventricles of MCU mutants, along with gene expression changes indicative of cell stress and altered cardiac structure and function. Using electrocardiography, we found that MCU hearts display conduction system defects and abnormal rhythm, with extended pauses resembling episodes of sinus arrest. Together, our findings suggest that proper mitochondrial Ca2+ homeostasis is crucial for maintaining a healthy adult heart, and establish the MCU mutant as a useful model for understanding the role of mitochondrial Ca2+ handling in adult cardiac biology.